The relationship between dental anxiety in children, adolescents and their parents at dental environment - Cristiane Meira Assunção; Estela Maris Losso; Roberto Andreatini; José Vitor Nogara Borges de Menezes (Wolters Kluwer Medknow Publications, 2013)
Purpose: The aim of the present study was to compare trait anxiety and dental anxiety among children, adolescents and their parents. Materials and Methods: A cross-sectional study was conducted involving 100 patients from the Pediatric Dentistry Clinic of the Federal University of Parana (Brazil) between the ages of 8 and 17 years (mean age: 10.3; standard deviation: 2.03) and their parents, who responded to Corah's Dental Anxiety Scale (DAS) and the Trait Anxiety Scale. The data were analyzed using the Mann-Whitney test, analysis of variance and both Pearson's and Spearman's correlation coefficients. Results: Ninety percent of children and adolescents and 76% of the parents had moderate anxiety based on the DAS score. Seventy-four percent of children and adolescents and 72% of the parents had moderate anxiety based on the Trait Anxiety Scale score. The trait anxiety and dental anxiety scores were correlated among the adults (rs = 0.64) and children (r = 0.52), whereas no correlation between scores was found among the adolescents. Associations were also found between children's trait anxiety and the dental and trait anxiety of their parents (both r = 0.43). Conclusions: A moderate degree of dental anxiety was prevalent among the children, adolescents and parents who took part in this investigation, with correlations demonstrated between some trait anxiety and dental anxiety scores.